MORPHOMETRY IN ADULT LONG-TAILED MONKEY POPULATION IN MOUNT PUSUK, NORTH LOMBOK DISTRICT - Prasetiyo, Dimas Kholis; Wandia, I Nengah; Bebas, Wayan (Buletin Veteriner Udayana, 2025)
Long-tailed macaque (Macaca fascicularis) or also known as cynomolgus monkey and crab-eating monkey is one type of macaque that lives in Southeast Asia. Morphometric measurements aim to determine the morphometry of the long-tailed macaque itself and to determine the morphometric differences between adult male and female long-tailed macaques living on Mount Pusuk, North Lombok. This study uses the Length Measurements method with the research object being 17 samples of long-tailed macaques. The samples were analyzed by finding the average of each morphometric measurement parameter and comparing the morphometry between adult male and female long-tailed macaques. The results of the calculation of the average morphometry of adult long-tailed macaques living on Mount Pusuk are face width 75.00 mm; head length 121.12 mm; upper arm length 129.94 mm; lower arm length 133.76 mm; thigh length 139.76 mm; calf length 148.00 mm; sitting height 420.00 mm; and tail length 502.06 mm. From the calculation results, the morphometric size between adult male and female long-tailed monkeys living on Mount Pusuk differs significantly (P <0.05). The difference that can be seen is that the morphometry of male long-tailed monkeys is larger than that of female long-tailed monkeys. Further research is needed on the morphometry of long-tailed monkeys on different parameters and from various age groups to determine the development and comparison of long-tailed monkey morphometry.